Augmenting the flipped classroom experience by integrating Revised Bloom's Taxonomy: A faculty perspective. Issue 1 (4th April 2023) - SivaKumar, ArunKumar
Abstract: In a recent scenario, the Master of Business Administration (MBA) job placement rates have decreased since the pandemic started. MBA job placement rates are down since the pandemic started. What's most alarming: the decline in MBA jobs (34%) has been steeper than the decline in overall jobs (27%), for the period between May 2019 and May 2020. The mere delivery of theoretical concepts, lack of practical knowledge and lag in imbibing soft skills have been identified as hurdles in the progress of MBA education. Some of the predominant industry‐needed skills need to be improved among MBA students. To address this issue, the author suggests integrating flipped classrooms with the Revised Bloom's Taxonomy (RBT) as a new paradigm for delivering MBA education. The flipped classroom is a pedagogical approach in which direct instructions move from group learning to individual learning. This study primarily aims to understand the faculty perception of the pre‐, in‐ and post‐class activities facilitated using an integrated model of a flipped classroom and RBT (FC+RBT) among MBA students. The study's target population is the faculty members working in MBA institutions across Tamil Nadu, India. The findings of this study will be helpful for MBA institutions to enhance the quality of MBA education and empower management graduates to imbibe employability skills.